2020
DOI: 10.1037/pro0000274
|View full text |Cite
|
Sign up to set email alerts
|

Blessing or BS? The therapy experiences of transgender and gender nonconforming clients obtaining referral letters for gender affirming medical treatment.

Abstract: Many transgender and gender nonconforming (TGNC) clients seek to obtain referral letters for gender affirming medical treatment from their mental health providers, but little is known about how the process of obtaining referral letters impacts TGNC clients' therapy experiences. We conducted semistructured interviews with 15 TGNC individuals who obtained a referral letter for gender affirming medical intervention from their therapists. Thematic analysis revealed 2 core themes: (a) "bullsh ‫ء‬ t" (or "BS") parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The necessity of preoperative mental health referral letters before gGAS has been heavily debated. [16][17][18] Some authors have suggested alternative patient-centered approaches to determining readiness for gGAS. 19 Regardless of whether one supports using mental health referral letters at all in the surgical transition process (such as before the first stage of primary gGAS), our patient experience has shown that additional referral letter requirements for staged or revision gGAS is particularly burdensome and unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The necessity of preoperative mental health referral letters before gGAS has been heavily debated. [16][17][18] Some authors have suggested alternative patient-centered approaches to determining readiness for gGAS. 19 Regardless of whether one supports using mental health referral letters at all in the surgical transition process (such as before the first stage of primary gGAS), our patient experience has shown that additional referral letter requirements for staged or revision gGAS is particularly burdensome and unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of preoperative mental health referral letters before gGAS has been heavily debated 16‐18 . Some authors have suggested alternative patient‐centered approaches to determining readiness for gGAS 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations